2018
DOI: 10.1111/tpj.14074
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic regulation of PIF5 by COP1–SPA complex to optimize photomorphogenesis in Arabidopsis

Abstract: Light signal provides the spatial and temporal information for plants to adapt to the prevailing environmental conditions. Alterations in light quality and quantity can trigger robust changes in global gene expression. In Arabidopsis thaliana, two groups of key factors regulating those changes in gene expression are CONSTITUTIVE PHOTOMORPHOGENESIS/DEETIOLATED/FUSCA (COP/DET/FUS) and a subset of basic helix-loop-helix transcription factors called PHYTOCHROME-INTERACTING FACTORS (PIFs). Recently, rapid progress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 73 publications
(121 reference statements)
3
53
0
Order By: Relevance
“…HY5/HFR1/LAF1 and others) in the dark (Hoecker, 2017). However, a few reports showed that PIFs are less abundant in cop1 mutants (Bauer et al, 2004;Pham et al, 2018a;Shen et al, 2008;Xu et al, 2017;Zhu et al, 2015) and also to a lesser extent in spaQ mutants (Leivar et al, 2008;Ni et al, 2014;Pham et al, 2018a), suggesting that the instability of PIFs contributes to the cop phenotypes of these mutants. Here, we show that the gene expression signature of cop1 and spaQ overlaps with pifQ in the dark, with preferential targeting of PIF direct target genes, suggesting that the cop phenotype of cop1 and spaQ is partly due to a reduced level of PIFs in these backgrounds.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…HY5/HFR1/LAF1 and others) in the dark (Hoecker, 2017). However, a few reports showed that PIFs are less abundant in cop1 mutants (Bauer et al, 2004;Pham et al, 2018a;Shen et al, 2008;Xu et al, 2017;Zhu et al, 2015) and also to a lesser extent in spaQ mutants (Leivar et al, 2008;Ni et al, 2014;Pham et al, 2018a), suggesting that the instability of PIFs contributes to the cop phenotypes of these mutants. Here, we show that the gene expression signature of cop1 and spaQ overlaps with pifQ in the dark, with preferential targeting of PIF direct target genes, suggesting that the cop phenotype of cop1 and spaQ is partly due to a reduced level of PIFs in these backgrounds.…”
Section: Introductionmentioning
confidence: 95%
“…Previously, we and others showed that the PIF levels in cop1 and spaQ mutants are reduced compared with wild type in the dark (Bauer et al, 2004;Leivar et al, 2008;Pham et al, 2018a;Zhu et al, 2015). To systematically analyze PIF levels without the transcriptional regulation in these mutants, we crossed the overexpression lines of tagged PIF1, PIF3, PIF4 and PIF5 using the constitutively active 35S promoter in cop1-4, TAP-PIF1 and PIF5-Myc in spaQ mutant backgrounds, and performed immunoblots for protein levels.…”
Section: Cop1 and Spa Positively Regulate Pif Protein Level In Darknessmentioning
confidence: 99%
“…PIF3 is degraded by CUL3 LRB and PIF4 by CUL3 BOP ; PIF1 is also degraded by CUL1 CTG10 and PIF3 is also degraded by CUL1 EBF1/2 . In the highlighted paper (Pham et al ., 2018b) and as illustrated schematically in the left panel of Figure , Enamul Huq's group demonstrate that CUL4 COP1‐SPA is necessary for the red light‐induced degradation of PIF5.…”
mentioning
confidence: 92%
“…PIF3 is degraded by CUL3 LRB and PIF4 by CUL3 BOP ; PIF1 is also degraded by CUL1 CTG10 and PIF3 is also degraded by CUL1 EBF1/2 . In the highlighted paper (Pham et al, 2018b) and as illustrated schematically COP1 SPA COP1 SPA PIF5 Growthpromo ng genes Protein degradation PIF5 Figure 1. Schematic showing that the COP1-SPA complex promotes PIF5 ubiquitination and degradation during early light responses (left panel) but also controls hypocotyl growth under diurnal conditions by stabilizing PIF5, which can then activate the expression of growth-promoting genes at night (right panel).…”
mentioning
confidence: 99%
See 1 more Smart Citation